2019
DOI: 10.1021/acs.nanolett.9b03507
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Hollow Microgels That Can Adapt Their Size, Shape, and Softness

Abstract: The development of soft anisotropic building blocks is of great interest for various applications in soft matter. Furthermore, such systems would be important model systems for ordering phenomena in fundamental soft matter science. In this work, we address the challenge of creating hollow and anisotropically shaped thermoresponsive microgels, polymeric networks with a solvent filled cavity in their center that are swollen in a good solvent. Sacrificial elliptical hematite silica particles were utilized as a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 67 publications
3
53
0
Order By: Relevance
“…This is most likely related to the cavity. The latter gives the polymeric network an additional possibility to swell: not only toward the outer, but also toward the inner periphery [19,20,43]. The swelling ratio of Q(Hollow)= 2.00 ± 0.06 agrees with previous studies on hollow pure pNIPAM microgels with a cross-linking density of 5 mol% [42].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is most likely related to the cavity. The latter gives the polymeric network an additional possibility to swell: not only toward the outer, but also toward the inner periphery [19,20,43]. The swelling ratio of Q(Hollow)= 2.00 ± 0.06 agrees with previous studies on hollow pure pNIPAM microgels with a cross-linking density of 5 mol% [42].…”
Section: Resultssupporting
confidence: 88%
“…An intact cavity is crucial for storage applications. Its size can be tuned by the choice of the sacrificial core [22,42,43], the composition of the polymer shell [19,20], and the environmental constraints as adsorbed to interfaces [44][45][46] or entrapped in highly crowded solutions [42,47].…”
Section: Introductionmentioning
confidence: 99%
“…Similar considerations should be extended to microgels in bulk conditions, for which high-density states still require appropriate theoretical assessment. The analysis can be further broadened to other microgel topologies that have recently gained considerable attention, such as hollow [88], ultra-low-cross-linked [28], or anisotropic ones [89].…”
Section: Discussionmentioning
confidence: 99%
“…[30] Recent progress in synthesis enabled preparation nanogels with internal compartments and various shapes. [31][32][33][34][35] Furthermore,i sw as observed that the extreme softness of ultra-low cross-linked (ULC) nanogels leads to unique properties. [36] ULC nanogels exhibit high swellability and flexibility.…”
Section: Introductionmentioning
confidence: 99%